2009
DOI: 10.5021/ad.2009.21.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi Sarcoma after Corticosteroid Therapy for Idiopathic Thrombocytopenic Purpura

Abstract: Fig. 1. (A)Multiple, dark-red colored nodules on the extremities that were several centimeters in size. (B) After the cessation of corticosteroids for 6 months, the skin nodules decreased in sized and number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Incidence of the KS in South Korea is very low and thus most of the researches were case reports [8,9]. Considering geographic variation of the KS, it would be important to review the treatment in a single-race group.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence of the KS in South Korea is very low and thus most of the researches were case reports [8,9]. Considering geographic variation of the KS, it would be important to review the treatment in a single-race group.…”
Section: Introductionmentioning
confidence: 99%
“…[293031] The co-occurrence of iatrogenic KS with idiopathic thrombocytopenic purpura receiving SC treatment was limited to only a few cases reported previously with no risk factor other than corticosteroid-induced immunosuppression, as in one of our iatrogenic KS patients. [32]…”
Section: Discussionmentioning
confidence: 99%
“…Noor Akmal and Abdul Wahab [ 16 ] reported findings on a patient who developed Kaposi’s sarcoma during corticosteroid therapy for ITP. Choi et al reported that Kaposi’s sarcoma occurred during immunosuppressive medication, including corticosteroid therapy for ITP, which has an unpredictably poor prognosis [ 66 ].…”
Section: Immune Thrombocytopenia and Malignancymentioning
confidence: 99%